2002
DOI: 10.1080/135502802317247820
|View full text |Cite
|
Sign up to set email alerts
|

Lack of nitric oxide synthase type 2 (NOS2) results in reduced neuronal apoptosis and mortality following mouse hepatitis virus infection of the central nervous system

Abstract: The role of nitric oxide synthase type-2 (NOS2)-derived nitric oxide (NO) in the pathogenesis of mouse hepatitis virus (MHV)-induced central nervous system disease was examined. Infection of NOS2 knockout ((-/-)) and NOS2(+/+) mice with MHV resulted in similar kinetics of viral clearance from the brain and comparable levels of demyelination. MHV-infected NOS2(-/-) mice displayed a marked decrease in mortality as compared to infected NOS2(+/+) mice that correlated with a significant decrease (P < or = 0.001) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 35 publications
0
21
0
1
Order By: Relevance
“…Theiler's murine encephalomyelitis virus (Rubio et al, 2003) and Sindbis virus (Kimura and Griffin, 2003) were also reported to induce apoptosis, with most of the infected cells not showing hallmarks of apoptosis, as we also observed following HCoV-OC43 infection. The murine counterpart of HCoV-OC43, MHV, was also reported to induce apoptosis in mouse brain (Chen and Lane, 2002;Wu and Perlman, 1999;Schwartz et al, 2002). Apoptosis induced by coronaviral infection could be associated with HCoV-mediated neuropathogenesis by killing cells or by disseminating virus while limiting inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Theiler's murine encephalomyelitis virus (Rubio et al, 2003) and Sindbis virus (Kimura and Griffin, 2003) were also reported to induce apoptosis, with most of the infected cells not showing hallmarks of apoptosis, as we also observed following HCoV-OC43 infection. The murine counterpart of HCoV-OC43, MHV, was also reported to induce apoptosis in mouse brain (Chen and Lane, 2002;Wu and Perlman, 1999;Schwartz et al, 2002). Apoptosis induced by coronaviral infection could be associated with HCoV-mediated neuropathogenesis by killing cells or by disseminating virus while limiting inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…In consequence, nitric oxide-derived oxidants are more likely to cause nonspecific nitro-oxidative damage in virusinfected tissue than to eliminate the virus [47][48][49]. Accordingly, it has been reported that infection of iNOS knockout (−/−) and iNOS (+/+) mice with MHV resulted in similar kinetics of virus clearance, but in reduced neuronal apoptosis and mortality [50]. We did not follow the kinetics of virus clearance in our experimental setting, but we did show that 7 days after infection, tempol reduced viral load, iNOS expression, and CNS damage.…”
Section: Discussionmentioning
confidence: 99%
“…HCoV-OC43 was previously reported to induce apoptosis in MRC-5 cells, a lung cell line 11 but not in infected human monocytes/macrophages, unlike the infection observed with strain 229E. 12 The murine counterpart of HCoV-OC43, MHV, was reported to induce apoptosis in 17Cl-1 cells, a murine fibroblast cell line 13 and in mouse brain neurons 14,15 in addition to macrophage/microglial cells, astrocytes and oligodendrocytes. 16,17 And recently, SARS-CoV was shown to induce apoptosis of Vero E6 cells.…”
Section: Discussionmentioning
confidence: 99%